Wideband textile antenna for wearable application - Yaziz, N. S. M. (Institute of Electrical and Electronics Engineers Inc., 2016)
This paper describe the design simulation and fabrication of wideband textile antenna. A rectangular monopole planar antenna with h slot is proposed in this paper. The antenna is made from Fleece fabric as a substrate and Shieldit fabric material as conductive element of the antenna. The optimization of the design has been done using CST Software simulation. The simulated results show that the antenna is operating between 1.8 GHz and 5 GHz while the measured results is between 2 GHz and 4.5 Hz. The experimental are carried out in free space with different orientations of the antenna. The radiation pattern of the antenna is nearly omnidirectional. From the measurements results, the antenna can be used at 2.3 GHz and 3.5 GHz (WiMAX), 2.45 GHz (WiFi) and 2.6 GHz (LTE).